Arbuscular Mycorrhizal Biofertilizers Sources in the Potato (Solanum Tuberosum) Plant show Interactions with Cultivars on Yield and Litter-bags Spectral Features - Volpato, Silvia; Masoero, Giorgio; Giovannetti, Giusto; Nuti, Marco (Journal of Agronomy Research, 2020)
Four strains of Arbuscular Mycorrhizal (AM) biofertilizer fungi, combined with two potato cultivars, were in-field tested in a four-replicate arrangement in a factorial experiment. As far as general combinability is concerned, cv. Agria was more responsive to different inocula (yield +5.56%, P 0.02) and to  two strains in particular (+8%). On the other hand, the results with Innovator, a cultivar that yields 33% less than Agria, showed a significant reduction in the number of tubers for three AM strains, thus proving a clear genetic Biofertilizer * Cultivar interaction. The study of hay litter-bags has shown a high NIR spectral fingerprint for the Cultivar factor (81%), while the Inoculation factor showed a higher spectral fingerprint in Agria (76%) than in Innovator (65%). The Substrate Induced Respiration predicted from the NIR-SCiO spectra of the litter-bags was significantly increased after inoculation (+6.3%, P 0.04), but appeared lower for Agria (-5.4%) vs. Innovator (P 0.05), with a non-significant interaction. The obtained results show that the adaptation of the AM strains to the genetics of potato cultivars  is a first step toward reducing chemical inputs, with consequent benefits for the environment, but without an excessive reduction in yield. The litter-bag technique can therefore be recommended for a simplified monitoring of the complicated plant-mycorrhizosphere relationship.
Keywords: Arbuscular Mycorrhizal; Biofertilizer; Potato; Cultivar; Yield